2008
DOI: 10.1093/rpd/ncn073
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose from a linear slit scanning X-ray machine with full-body imaging capabilities

Abstract: Doses for a range of examinations and views using digital X-ray equipment with full-body linear slit scanning capabilities (Statscan) have been compared with those from other published studies. Entrance doses (free-in-air) were measured using a dosimeter, and effective doses were generated using a Monte Carlo simulator. Doses delivered by the linear slit scanning system were significantly lower than those from conventional X-ray equipment. Effective doses were between 9 and 75% of the United Nations Scientific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…An X-ray detector unit (scintillator array) is fixed on the other end of the C-arm. The spatial resolution can be selected from 1.04 up to 5.0 line pairs/mm [13]. The C-arm is rotated axially around the patient for scanning at different angles.…”
Section: Linear Slot X-ray Scanning (Ls)mentioning
confidence: 99%
See 1 more Smart Citation
“…An X-ray detector unit (scintillator array) is fixed on the other end of the C-arm. The spatial resolution can be selected from 1.04 up to 5.0 line pairs/mm [13]. The C-arm is rotated axially around the patient for scanning at different angles.…”
Section: Linear Slot X-ray Scanning (Ls)mentioning
confidence: 99%
“…Our study has the following limitations: Retrospectively, we were not able to recover the effective dose of the LS scans. The entrance dose for full-body anterior/posterior is 0.2 mGy and full spine lateral is 0.75 mGy [13]. Wedegärtner et al [26] analyzed the effective dose applied to multiple trauma patients.…”
mentioning
confidence: 99%
“…7 The utility of the Statscan in the trauma setting has been demonstrated. [8][9][10] In a study on triage evaluation of polytrauma patients, the Statscan afforded superior visualisation of the paediatric trachea and main bronchi on AP supine chest radiographs, compared with CR.…”
Section: Introductionmentioning
confidence: 99%
“…This comes as no surprise. Irving et al 11 examined a modern linear slit scanner and found the effective dose for a head anteroposterior scan to be a third of the typical conventional radiography dose. For the same scanner, Maree et al 12 found significantly lower doses for all pediatric examinations compared with conventional radiography.…”
Section: Discussionmentioning
confidence: 99%